Discussion on new climate issues: Eco-design, circular alternative and Intrusion Prevention System (IPS) - Kada, Kaddour Benabbad (The International tax journal, 2025)
An eco-inclusive environment is about interconnecting public services with the environmental concerns. It is obvious that the urban expansion makes higher demand on a wide range of resources. Predicting the future technological mutations and their environmental impacts are at the core of any impact assessment of a newly-designed product as the evolution waves are becoming shorter with the events of automation and nanotechnologies. The Eco-Design is aiming to contribute in more circular economy which eliminates the "business-as-usual" harming effects. In practice, a greater awareness that the circular economy model must prevail over the classical business as usual model by adopting innovative green design as a starting point. Likewise, a sustainable adaptation to climate change pressures is possible by rethinking the recycling materials' proceeds and mitigating waste. through the upgrading of the existing products.